Dams and Displacement in Turkey and Pakistan - Hadi, Abdul (European Journal of Economics and Business Studies, 2017)
The development policy makers in both Turkey and Pakistan believe that the construction of dams would bring development and prosperity in their countries. Believing in this development model, so far many dams have been constructed and others are either under the construction or in planning process in both countries. The evidences are steadily mounting and reveal that the benefits of dams have been over exaggerated and their social and ecological costs were grossly underestimated. Construction of dams resulted in the displacement of thousands of people in both countries. With the help of existing literature and studies, this study has been carried out and focused on the living conditions of displacees after the construction of dams in both countries. This study has found that in the case of Turkey due to inequitable land distribution major benefits of dams mostly beneficiaries of dam projects are people who are already well-off and but the people who were displaced due to dams and also were landless are living worse life compared with their previous living conditions. In Pakistan, there were resettlements plans for reservoir-induced displacees but not for deltaic people who were the most affectees. The reduction in fresh water flow and the encroachment of sea have brought destruction to both delta and deltaic people. In the absence of any resettlement plan and compensation, these people are forced to live in the slum areas of big cities and facing miserable poverty and psychological problems.
Keywords: Dams, Displacement, Environmental Justice, Turkey, Pakistan